Jean-Laurent Rosenthal, R. Bin Wong. Before and Beyond Divergence: The Politics of Economic Change in China and Europe. Cambridge, MA, Harvard University Press, 2011, XI, 276 págs. - Álvarez Klee, Roser (Investigaciones de Historia Económica, 2019)
Sin resumen